The Reverse Engineering on Golok Banten Slash Type - Haryadi; Rifki Ari Darmawan Darmawan (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2021)
Making tools such as machetes in the Banten area is still widely done, machetes are produced from the process of forging conventionally using a hammer carried out by a blacksmith. Work as a blacksmith in Banten areas is passed down through generations as a cultural heritage, but over time the machete of traditional blacksmith results began to be shifted with modern machetes. The purpose of this research is to find out the configuration and characteristics of these two types of Banten cultural heritage machetes, devoted to slash-type machetes. Research is carried out starting from identifying problems, interviews, recording configurations, and finding and analyzing the styles that occur in the process of release. The results of this research produced configuration data and characteristics of slash machetes so that the data can be information for the public and companies who if want to make a machete Banten slash type.